Comparison of Human Nature in Masnavi and Nasirean Ethicsof Khajeh Nasir al-Din Tusi - Nourazar, Shapour; Reza Shadmanaamen, Mohammad (Revista de la Universidad del Zulia, 2019)
Human in nature has no goal in life but happiness and success; happiness  is a form of life that men aspire to and are fascinated with it. Man in his nature requires basically some issues which include: growing body, economic need, sexual need, beauty, and moral need, formation of the physical body of a man is related to the statue or the human body, not the man himself, and only when a soul has been blown in him, he finds a human figure and he is called human. Maulana considered human as a being with theanthropic dimension thathe says opposing forces in human existence is a sign of balance in creation and believed that human is the goal of creation and all creatures have been created so that onlya man becomes matured, and the biggest obstacle to growth and perfection of human in Rumi’s perspective is sensuality and egotism. Khaje Nasir al- Din Tusi believes that human is a symbol of the perfection of God’s acts, and human perfection is realized with health, happiness, blessings, mercy, eternal life, true happiness and in his perspective, religious mystical knowledge fosters man and all the behaviors and movements of human that god possesses.